The Need for Self-Actualization of the Main Character in Animated Film “Omoide No Marnie” - Ardhia Nandita Dikariasty; Ayu Putri Seruni (Universitas Cokroaminoto Palopo, 2022)
The Need for Self-Actualization of the Main Character in Animated Film “Omoide No Marnie” is a descriptive qualitative research through Abraham Maslow's humanistic psychology in a literature study method with the object of research “Omoide no Marnie” animated film. The purpose of this research is to reveal the fulfillment of all the basic needs of the main character that support the main character's self-actualization at the end of the story. The results of the research found are the achievement of the main character's self-actualization through the fulfillment of basic needs while the main character is in Kushiro. Self-actualization needs are motivated by the satisfaction of lower needs that can motivate humans to fulfill higher needs above them. The higher the needs that can be met, the more the person's quality will develop. These basic needs include physiological needs, safety needs, social and love needs, self-esteem needs, and self-actualization needs. In the film, it is explained that the main character can actualize herself after all her multilevel needs are fulfilled through a series of events that occured.